Self-care of people with Diabetes mellitus and psychiatric comorbidities: Integrative review (Research, Society and Development, 2023)
To identify in the scientific literature the knowledge produced about self-care generated by Diabetes Mellitus (DM) in people with psychiatric comorbidities. Integrative review using database searches: Medical Literature Analysis and Retrieval System online (MedLine), Latin American and Caribbean Literature in Health Sciences (LILACS) and Embase, and the electronic libraries Regional Portal Virtual Health Library (BVS), Scientific Electronic Library Online (SCIELO) and Periódico Capes, obtained a total of 6 reviewed articles, published between 2017 and 2022. In the synthesis of the results, it was verified that the associated comorbidities influence the care and treatment goals, therefore people with mental disorders need greater support for the improvement of self-care. The integration of the references made made it possible to show that psychiatric comorbidities mask and/or exacerbate the symptoms of DM, and in order to have an effective self-care, the person must pay attention to the signs of his organism and have access to relevant information about his health condition and demand for care, but there is a lack of studies and development of educational programs.